Combining ability for biological nitrogen fixation traits and yield components in black gram [Vigna mungo (L.) Hepper] - Thomas, Beena; Sreekumar, S.G. (Journal of Tropical Agriculture, 2006)
Twenty three black gram genotypes comprising of five lines with nitrogen fixing capacity, three high yielding testers and their 15 cross combinations were evaluated in randomized block design with three replications during summer 1995-96, at the Department of Plant Breeding and Genetics, College of Agriculture, Thiruvananthapuram. The best general combiners for important biological nitrogen fixation traits were COBG 305 and Pant U 19 among lines and T 9 among testers. Pant U 19 x T 9 was the best specific cross combination for the above traits. For number of pods and grain yield per plant, WBG 13 and T 9 were the best general combiners and hybrids, LEG 17 x VBN 1 and WBG 13 x AKU 4 were the best specific combinations